Factors Influencing University Student’s Readiness toward the Working World - Nadia Apriliana; Ika Indriasari; Rita Meiriyanti (Almana : Jurnal Manajemen dan Bisnis, 2022)
Abstract: The era of globalization that is increasing and has strong competitiveness between companies encourages every university to improve the quality and readiness of students to enter the world of work. Based on this, this study aims to test and analyze the influence of mastery of technology, development of work skills, and soft skills on student work readiness. The population used in this study was students of the Management Study Program, Faculty of Economics and Business, PGRI Semarang University Class of 2018-2019 which amounted to 428 students, and a research sample of 208 respondents was obtained. The sampling technique used is purposive sampling. Based on the results of research using the t-test (partial), it was found that mastery of technology affects job readiness, development of work skills affects job readiness, and soft skills do not affect job readiness. The results in the f test (simultaneous), it was found that mastery of technology, development of work skills, and soft skills simultaneously affect job readiness.